Transport and sedimentation of microplastics by turbidity currents: Dependence on suspended sediment concentration and grain size - Marianna Soler; Jordi Colomer; Florian Pohl; Teresa Serra (Environment International)
Using lock-exchange experiments, this study investigates the transport and sedimentation of microplastics (MPs) via turbidity currents. Two hypotheses were tested: MP sedimentation is influenced by suspended sediment concentration and grain size. Utilizing flows with different sediment concentrations and grain sizes in combination with three different MPs (PET fibers, melamine, and PVC fragments), the experiments revealed distinct sedimentation patterns: higher sediment concentrations enhance MP transport, and turbidity currents with finer sediments transported MPs over greater distances, highlighting the importance of sediment characteristics to predict MP distribution by such flows. Further, MP sedimentation patterns varied in dependence on MP-particle shape, size, and density, highlighting the crucial role of MP particle properties in determining MP distribution in turbidites. These findings enhance our understanding of the mechanisms controlling the spatial distribution of MPs in marine sedimentary-environments and underscores the importance of considering both hydrodynamic and particle-specific factors when addressing the complex behaviour of MPs.